Role of Ethyl Pyruvate in Systemic Inflammatory Response and Lung Injury in an Experimental Model of Ruptured Abdominal Aortic Aneurysm. (19th January 2014) - Pulathan, Zerrin; Altun, Gökalp; Hemşinli, Doğuş; Menteşe, Ahmet; Yuluğ, Esin; Civelek, Ali
Abstract : Objectıve . The purpose of this study is to evaluate the effect of ethyl pyruvate (EP) on systemic inflammatory response and lung injury in an experimental rat model of ruptured abdominal aortic anurysm (RAAA). Methods . Anaesthetized 30 Sprague-Dawley male rats were randomized to sham (Sh n : 6 ) (Sh + EP n : 6 ) or shock and clamp (S/C) groups (S/C n : 9 ) (S/C + EP n : 9 ). In the S/C and S/C + EP groups, hemorrhagic shock, lower torso ischemia, and reperfusion were created, S/C group was given 1 mL saline and S/C + EP group was given 40 mg/kg EP. At the end of reperfusion process some biochemical and histological parameters were studied in serum and lung tissues. Results . An increase was observed in all parameters except interleukin-6 (IL-6) in the S/C group in comparison to the sham groups. In the S/C + EP group, serum myeloperoxydase (MPO), malondialdehyde (MDA), and tumor necrosis factor alpha (TNF- α ) as well as lung MPO and MDA values decreased significantly (P < 0.016 ). In the lung tissues, histological injury scores and lung tissue wet/dry ratio were significantly decreased in the S/C + EP group as compared to the S/C group (P < 0.016 ). Conclusions . Ethyl pyruvate may reduce systemic inflammatory response and lung injury which resulted from shock and ischemia/reperfusion in an experimental model of RAAA.